A 'Great Affective Divide': How Gay Singaporeans Overcome Their Double Alienation. Issue 1 (2nd January 2016) - Tan, Chris K. K.
ABSTRACT: Since its independence in 1965, Singapore has been trying to unify its diverse ethnic, linguistic, and religious communities under one coherent national identity. Queer Singaporeans, however, suffer from a double alienation from the nation. While socially ostracised by the existing anti-sodomy Section 377A and the queer-unfriendly state policies that it justifies, they also suffer from that inability to identify with the nation called the 'Great Affective Divide'. In this essay, I aim to achieve two goals. Firstly, I invoke the idea of cultural citizenship as I ethnographically investigate the efforts that queer Singaporeans make to overcome their national estrangement, particularly an event called 'Pink Dot'. While such efforts do not receive universal support from queers, they are essential in the development of a better understanding of it means to be citizens of Singapore. Secondly, rather than wanting to remain socially marginal and critical of the norm, queers actually express their desire for national inclusion through Pink Dot. Yet, I argue that it would be erroneous to read this desire as 'homonationalism'. As such, Pink Dot provides a fertile example that counters the conventional view within Queer Studies that queers always resist the hetero-patriarchal norm.